Sur quelques échos de Flaubert dans l’œuvre de Matilde Serao - Rosa Maria Palermo Di Stefano (Flaubert: Revue Critique et Génétique)
The work of the Neapolitan journalist and novelist Matilde Serao (1856-1927) shows the influence of her time’s literary schools (Naturalism, Verism, Experimentalism), but also of authors such as Balzac and Flaubert. We will analyze in particular the relationship between Madame Bovary and Fantasia, illustrating how, in Matilde Serao’s novel, there are patent echoes of Flaubert’s text but also highlighting the deep differences between the two works.